Improvement of Vocational Training of Pupils in Secondary Schools - Samaridin Barakaevich, Karaev (International Journal of Psychosocial Rehabilitation, 2020)
This article reveals the process of research is to improve the process of vocational training in secondary schools. The tasks of the research are following as: improvement of mechanisms of vocational training of students based on the integration of technological and professional-psychological training; development of proposals for new occupations based on the needs of the socio-economic development of the regions; improving the technology of developing and applying a database of students' motivation, resilience, and career aspirations; improving students 'professional knowledge and skills through the development of teachers' professional abilities, skills and competencies. The article consists of from introduction, literature review, methodology of research, discussion, experimental work and conclusion.